2022
DOI: 10.3390/cells11213457
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin-Induced Down-Regulation of Placenta-Derived Exosomal miR-140-3p and miR-574-3p Promotes Umbilical Vein Endothelial Cells Proliferation, Migration, and Tube Formation in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) leads to poor pregnancy outcomes and fetoplacental endothelial dysfunction; however, the underlying mechanisms remain unknown. This study aimed to investigate the effect of placenta-derived exosomal miRNAs on fetoplacental endothelial dysfunction in GDM, as well as to further explore the role of chemerin to this end. Placenta-derived exosomal miR-140-3p and miR-574-3p expression (next-generation sequencing, quantitative real-time PCR), its interactions with cell function (Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Blood flow volume represents the physical aspect of foetal blood access. However, various biochemical substances in the blood play crucial roles as biological and chemical factors for foetal blood and nutrient acquisition, including vascular growth factors and blood sugar ( 32 , 33 ). Scholars from different countries have investigated the biochemical substances in foetal umbilical vein blood flow and concluded that multiple biochemical substances jointly affect foetal weight gain ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow volume represents the physical aspect of foetal blood access. However, various biochemical substances in the blood play crucial roles as biological and chemical factors for foetal blood and nutrient acquisition, including vascular growth factors and blood sugar ( 32 , 33 ). Scholars from different countries have investigated the biochemical substances in foetal umbilical vein blood flow and concluded that multiple biochemical substances jointly affect foetal weight gain ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, most radiation-modulating natural-product-regulated miRNAs (Table 3) are associated with exosome biogenesis and miRDB results for exosome biogenesismodulating targets. However, other miRNAs , such as miR-3960 [143], miR-6085 [144], miR-18a-5p [145], miR-22-3p [146], miR-126-3p [147], miR-137-3p [148], miR-122-5p [149], miR-23a-3p [150], miR-155-5p [151], miR-33a-5p [152], miR-574-3p [153], miR-132-3p [154], miR-211-5p [155], miR-375-3p [156], miR-181c-3p [157], miR-146a-5p [158], miR-542-3p [159], miR-877-3p [160], miR-192-5p [161], miR-451a [162], miR-215-5p [163], miR-99b-3p [164], miR-549a-5p [165], and miR-1247-5p [166], have only been reported in terms of exosome biogenesis-modulating effects, without available miRDB results for exosome biogenesis-modulating targets.…”
Section: Other Natural-product-regulated Mirnas May Have Exosome Biog...mentioning
confidence: 99%
“…Exosomal miR-33a-5p was present at only a low level in resistant colon cancer cells [152]. Placenta-derived exosomal miR-574-3p was underexpressed after chemerin, enhancing proliferation and angiogenesis for gestational diabetes mellitus [153]. Mesenchymal stem-cell-derived exosomal miR-132-3p improved proliferation, inhibited apoptosis in an in vitro inflammatory cell model, and reduced LPS-induced acute lung injury in mice [154].…”
Section: Other Natural-product-regulated Mirnas May Have Exosome Biog...mentioning
confidence: 99%